Candida endocarditis after heart surgery. Issue 4 (July 1968) - Conway, N.; Kothari, M. L.; Lockey, Eunice; Yacoub, M. H.
Abstract : Four new cases of Candida endocarditis after heart surgery are described and predisposing factors are discussed. Details are given of the one patient diagnosed in life and treated successfully with amphotericin B.